PCCI-DI Combustion Simulation for Significant Reduction of NOX and PM for GENSET Engine - Kinikar, Hemant A.; Patil, A.B. Kanase-; Thipse, S. S.; Jadhav, Tushar A. (International Journal of Membrane Science and Technology, 2023)
Improvements in engine combustion are required due to the stringent pollution norms. This can be achieved either by making improvements in the combustion or by equipping after-treatment devices to control engine emission levels. PCCI is one of the popular techniques used to enhance the combustion. In this work, Diesel-RK software is used for the simulation. The main and pre-injection timings are altered to give the benefits in power and emissions. Based on a literature survey, the fourth and fifth modes are finalized for PCCI combustion simulation. The amount of total fuel injected was kept the same to compare the performances in DI and PCCI modes. The simulation results show the reduction in soot (PM) and NOx simultaneously with the help of PCCI concept at lower BMEP levels. The results show a decrease in PM by up to 26%, a reduction in NOx by up to 30% and an increase in power by 2%.